A Agenda de Segurança Internacional no BRICS (2009-2019) - Ramos, Leonardo; Rocha, Pedro D. [UNESP]; Zahreddine, Danny (Instituto de Estudos Sociais e Políticos (IESP) da Universidade do Estado do Rio de Janeiro (UERJ), 2021)
Since its foundation in the late 2000s, BRICS was inclined to cooperate more intensely in what regards international political economy, especially topics concerned with international development. From the summits of Sanya (2011) and Delhi (2012), however, topics on international security started gradually to find its place among the group. Both summits are understood here as turning points and the later theme, BRICS Partnership for Global Stability, Security and Prosperity , as essential to the proposed argument. Having said that, the main goal of this article is to uncover the thickening of cooperation on international security among BRICS from 2009 to 2019. In order to do so, first it is debated its approach to the development-security nexus as well as its limits, and later a content analysis of the summits declarations is undertaken. Stands out from the analysis six thematic areas and inside each is highlighted the evolution of BRICS approach toward the topic.

Desde su creación en la segunda mitad de la década del 2000, predominaron en los BRICS discusiones relativas a la economía política internacional, especialmente aquellas ligadas al desarrollo internacional. A partir de las cúpulas de Sanya (2011) y Delhi (2012), sin embargo, cuestiones de seguridad internacional pasan también a tener paulatinamente un espacio dentro del grupo. Los encuentros son entendidos aquí como marco de este proceso y la temática del segundo, BRICS Partnership for Global Stability, Security and Prosperity, como esencial para el argumento propuesto. El objetivo general del artículo es analizar las discusiones sobre Seguridad Internacional dentro de las cúpulas de los BRICS de 2009 a 2019. Para cumplirlo, se discute la aproximación del grupo al nexo desarrollo-seguridad, así como los límites de esta aproximación y es realizado un análisis de contenido de las declaraciones de la cúpula de los BRICS. Se destacan en el análisis seis unidades temáticas y dentro de cada una se subraya la evolución de las discusiones y el abordaje que dio el grupo a cada una.

Depuis sa création dans la seconde moitié des années 2000, ont prédominé dans les BRICS les discussions concernant l’économie politique internationale, notamment celles liées au développement international. Mais depuis les sommets de Sanya (2011) et de Delhi (2012), les questions de sécurité internationale ont également progressivement gagné place au sein du groupe. Les réunions sont comprises ici comme un jalon de ce processus et le thème du deuxième, le BRICS Partnership for Global Stability, Security and Prosperity , est essentiel à l’argumentation proposée. L’objectif général de l’article est d’analyser les discussions sur la sécurité internationale dans le cadre des sommets des BRICS de 2009 à 2019. Pour y parvenir, l’approche du groupe sur le lien développement-sécurité est discutée, ainsi que les limites de cette approche, et une analyse du contenu des déclarations au sommet des BRICS est effectuée. Six unités thématiques ressortent de l’analyse et au sein de chacune d’elles, l’évolution des discussions et l’approche du groupe face aux problèmes sont mises en évidence.

Desde sua criação, predominaram no BRICS discussões relativas à economia política internacional, especialmente as ligadas ao desenvolvimento internacional. Entretanto, a partir das cúpulas de Sanya (2011) e Delhi (2012), questões de segurança internacional passaram a paulatinamente ocupar maior espaço dentro do grupo. Tais cúpulas são aqui entendidas como marco desse processo, e particularmente a temática da segunda, BRICS Partnership for Global Stability, Security and Prosperity, como essencial para o argumento proposto. O objetivo geral do artigo é analisar as discussões sobre segurança internacional dentro das cúpulas dos BRICS de 2009 a 2019. De modo a cumpri-lo, discute a aproximação do grupo ao nexo desenvolvimento-segurança, bem como os limites desta aproximação, e realiza uma análise de conteúdo das declarações de cúpula dos BRICS. Destacam-se na análise seis unidades temáticas e dentro de cada uma delas se sublinha a evolução das discussões e a abordagem do grupo às problemáticas.
The BRICS International Security Agenda (2009-2019)
La Agenda de Seguridad Internacional en el BRICS (2009-2019)
Keywords: BRICS; cooperation; international security; development; content Analysis; BRICS; cooperação; segurança internacional; desenvolvimento; análise de conteúdo